Aspectos econômicos da discriminação racial: implicações econômicas do racismo estrutural sob a ótica da economia institucional - Silva, Gracielle Maria da (2022)
The objective of this work is to carry out a historical and social analysis of racial discrimination as a determining factor of the social and economic vulnerabilities perceived by black people in Brazil, based on the analysis of the access of this segment of the population in the postAbolition labor market. This dissertation presents some evidences that may contribute to the analysis of the persistence of income differences of the black population segment in relation to other racial groups in Brazil. Some structural determinants, promoted by political, economic and cultural institutions that operate in order to maintain the current structure, favor the persistence of inequalities for this social group. Veblenian Institutional Economics (Old Institutional Economics) was used as a theoretical approach from which the persistence of the mentioned vulnerabilities is evaluated, in contrast to the neoclassical approach, commonly used by orthodoxy in the study of the Economics of Discrimination